2006
DOI: 10.1002/jrs.1637
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of inorganic pigments in ancient glass beads by means of Raman microspectroscopy, microprobe analysis and X‐ray diffractometry

Abstract: Ancient coloured glass beads from Sri Lanka and Oman were analysed by Raman microspectroscopy for non-destructive identification of inorganic pigments in the glass. Calcium phosphate (Ca 3 (PO 4 ) 2 ), cassiterite (SnO 2 ), cuprite (Cu 2 O) and a Pb(Sn,Si)O 3 -type lead tin oxide were found to be used as colouring agents. Moreover, a distinction between lead-based and alkali-based glass matrices could be made. Electron microprobe analysis and X-ray diffractometry were performed to show the capability of Raman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 14 publications
5
45
0
Order By: Relevance
“…The combination of Cu (blue for the sodium-potassium-calcium glass) and lead tin yellow type II to obtain a green colour has also been observed in green glass beads excavated in Sri Lanka. 18 In the spectrum of the orange bead, Raman bands originating from lead tin yellow type II can also be distinguished, but in addition a very strong signal at 113 cm 1 and a peak at 529 cm 1 are observed (Fig. 4(e)).…”
Section: Pigmentsmentioning
confidence: 94%
“…The combination of Cu (blue for the sodium-potassium-calcium glass) and lead tin yellow type II to obtain a green colour has also been observed in green glass beads excavated in Sri Lanka. 18 In the spectrum of the orange bead, Raman bands originating from lead tin yellow type II can also be distinguished, but in addition a very strong signal at 113 cm 1 and a peak at 529 cm 1 are observed (Fig. 4(e)).…”
Section: Pigmentsmentioning
confidence: 94%
“…In the Raman spectra, this lead may be displayed by a very typical band at 984 cm −1 (Colomban et al 2003), as shown in Fig. 7b, indicating that the glass matrix is formed by a network of two-dimensional chains of SiO 4 tetrahedra with mainly two non-binding oxygen atoms, in contrast to Na-and K-dominated glass with mostly one non-binding oxygen atom and a sheet-like network (Welter et al 2007). The growth of cuprite crystals is of course also depending on temperature treatment (Henderson 1985).…”
Section: Microcrystals As Opacifier and Colourantsmentioning
confidence: 96%
“…Nondestructive X-ray powder diffraction could be an appropriate method, but in the case of the mosaic glass, a high spatial resolution of the X-ray beam is essential, but not yet standard for most of the instruments. Alternatively, Raman microspectroscopy has turned out as a powerful method, which works non-destructively, fast, with high spatial resolution, and which allows for highly variable sample sizes (Welter et al 2007). For the studied glass fragments, the following colourants and opacifiers have been characterised: Calcium antimonate is typical for all the opaque white glass samples.…”
Section: Microcrystals As Opacifier and Colourantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glass beads, pearls, porcelain, pottery, textiles, ceramics, shards Ancient colored glass beads from Sri Lanka and Oman were analyzed by Raman micro-spectroscopy for the nondestructive identification of inorganic pigments in the glass by Welter et al 33 Calcium phosphate, cassiterite, cuprite and lead tin oxide were identified as coloring agents. A similar study for the elucidation of the pigments was done by Karampelas et al 34 on cultured freshwater pearls from the mollusk Hyriopsis cumingi.…”
Section: Art and Archaeology Pigments Paintsmentioning
confidence: 99%